A comparison of benzyl and 2-naphthylmethyl ethers as permanent hydroxyl protecting groups in the synthesis of α-galactoglycosphingolipids KRN7000 and PBS-57. Issue 4 (13th June 2017) - Yao, Dongming; Liu, Yichu; Gao, Qi; Sui, Qiang; Liu, Xiaoping; Ding, Ning
GRAPHICAL ABSTRACT: ABSTRACT: Due to the interest in the biological properties of marine derived α-galactoglycosphingolipids (α-GalGSLs), a lot of work has focused on the development of their synthesis. Here we conducted the direct comparison of benzyl and 2-naphthylmethyl (Nap) ethers as permanent hydroxyl protecting groups for the synthesis of KRN7000, as well as the practical synthesis of a biologically active α-GalGSLs PBS-57. This work further revealed the advantages of Nap ether over benzyl ether for permanent hydroxyl protection in the synthesis of α-GalGSLs.